Hierarchically structured V2O3/C microspheres: synthesis, characterization, and their electrochemical properties - Thauer, Elisa; Zakharova, G. S.; Deeg, Lukas; Zhu, Q.; Klingeler, Rüdiger (Electrochimica acta, 2021)
The V2O3/C composites have been successfully synthesized by a facile hydrothermal thermolysis method, employing vanadyl hydroxide as precursor and different carboxylic acids as both a carbon source and reducing agents. The morphology, structure, and composition of the obtained V2O3/C composites were investigated by X-ray diffraction, Raman spectroscopy, scanning and transmission electron microscopies, physical sorption, thermogravimetric analysis coupled with mass-spectrometry, and elemental analysis. The as-prepared V2O3/C composites consist of hierarchically structured microspheres, either with core-shell or solid architecture depending on the used carboxylic acid. When used as anode for lithium-ion batteries, the V2O3/C spheres deliver very good electrochemical performance with high specific capacity, great cyclic stability, and high rate capability. The large capacitive current contribution favors superior lithium storage kinetics compared to more compact chunk-shaped V2O3/C materials. In particular, the composite prepared with tartaric acid exhibits a high reversible capacity of 454 mAh g−1 after 100 cycles at 100 mA g−1.